2022
DOI: 10.3390/ma15217798
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Strength Gain in Sandy Soil Stabilised with Mixed Binders Evaluated by Elastic P-Waves during Compressive Loading

Abstract: This paper addresses the problem of stabilisation of poor subgrade soil for improving its engineering properties and stiffness. The study aim is to evaluate the effects from single and mixed binders on the gain of strength in sandy soil over the period of curing. We propose an effective non-destructive approach of using P-waves for identifying soil strength upon stabilisation. The growth of strength and stiffness is strongly dependent on time of curing and type of the stabilising agents which can include both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies on the evaluation of the effects of various mixtures demonstrated [57] that GGBFS contributes the most to the compressive strength development in expansive clayey soil, followed by OPC. Moreover, blended mixtures of cement with GGBFS and lime with GGBFS perform better than single binders.…”
Section: Essentials On Binder Selectionmentioning
confidence: 97%
“…Previous studies on the evaluation of the effects of various mixtures demonstrated [57] that GGBFS contributes the most to the compressive strength development in expansive clayey soil, followed by OPC. Moreover, blended mixtures of cement with GGBFS and lime with GGBFS perform better than single binders.…”
Section: Essentials On Binder Selectionmentioning
confidence: 97%
“…The equipment for measuring P-wave velocity was readily available at SGI, and the methods used followed a process of seismic measurements to evaluate the P-wave velocity of the specimens. This process was conducted in accordance with the existing workflow scheme [109].…”
Section: Seismic Measurementsmentioning
confidence: 99%
“…The applicability of this technique for soil improvement have been seen in several studies [23][24][25][26][27], however, none of these have studied the strength development over time and how this varies depending on soil and binder type, e.g., the effectiveness of different industrial by-products. One exception is the work by Lindh [28][29][30]; however, the strength difference over time for varying by-products was not studied. This note presents a study on the strength development over time using the industrial by-products GGBS and CKD in combination with C. Two natural soft Swedish clays are improved; one inorganic clay simply referred to as 'clay', and one organic clay referred to as 'gyttja'.…”
Section: Introductionmentioning
confidence: 99%